Research progress on molecular mechanisms of general anesthetic-induced neurotoxicity and cognitive impairment in the developing brain - Wang, Jiaojiao; Liu, Zhihui (Frontiers in Neurology, 2022)
General anesthetics-induced neurotoxicity and cognitive impairment in developing brains have become one of the current research hotspots in the medical science community. The underlying mechanisms are complex and involve various related molecular signaling pathways, cell mediators, autophagy, and other pathological processes. However, few drugs can be directly used to treat neurotoxicity and cognitive impairment caused by general anesthetics in clinical practice. This article reviews the molecular mechanism of general anesthesia-induced neurotoxicity and cognitive impairment in the neonatal brain after surgery in the hope of providing critical references for the treatments of clinical diseases.